Pakottamalla vai tahdonvastaisesti? Uusi seksuaalirikoslainsäädäntö käräjäoikeuksissa - Tapanila, Antti (Lakimies, 2024)
Forced or involuntary? New sexual offences legislation in district courts Chapter 20 of the Criminal Code, entitled Sexual Offences, has been completely reformed in Finland as of the beginning of 2023. There are three objectives behind the new legislation. The first objective was to change the definition of rape to be consent-based. The legislation in force in the past required violence or the threat of violence. In the new law, it is sufficient that sexual intercourse is contrary to the person’s will. The second aim of the reform was to separate sexual offenses against children from those against adults at regulatory level. The third goal of the legislature was to increase penalties, especially for sexual offences against children. For the article, 26 convictions were selected from five different district courts, representing a significant proportion of the convictions in which the new Chapter 20 of the Penal Code has been applied. On the basis of the cases, conclusions can be drawn as to how the district courts have applied the new legislation and whether the legislator’s objectives have been met in case law. In the majority of the district court’s decisions, the rapes had been carried out using methods that would have met the criteria of the previous version of Chapter 20 of the Criminal Code. The actions involved either physical coercion or were directed at sleeping or passed out injured parties. The verdicts suggest that prosecutors had not sought punishment for the acts based solely on a lack of consent. Crimes against children were assessed in the convictions on the basis of the different legal characteristics of the offences. Similar crimes were not previously likely to have been interpreted as coercion of the injured party to engage in sexual activity. The change in the law thus had a concrete effect on the decisions of the courts. Sentencing practice suggested, especially in rape offences against adults, that the reform of the law has not had a severe effect on sentences for rape. A significant proportion of the sentences were still conditional prison sentences of less than two years.